An empirical investigation of part-whole hierarchical relations. Issue 1 (2nd January 2018) - Stewart, Ian; Slattery, Brian; Chambers, Michael; Dymond, Simon
ABSTRACT: Previous research has shown classification type ("class/member") hierarchical responding as relational framing. The aim of this study was to use the same paradigm to investigate analysis type ("part-whole") hierarchical responding. A total of 10 participants were exposed to (1) a procedure involving non-arbitrarily related multi-dimensional stimuli, the aim of which was to establish two arbitrary shapes as contextual cues for "part of" and "includes" relational responding respectively; and (2) a procedure that employed these cues to establish a network of arbitrary stimuli in particular hierarchical relations with each other and then test for derivation of further untrained hierarchical relations as well as for transformation of functions (TOF). Resultant patterns of relational framing consistently showed features of asymmetrical mutual entailment and transitive combinatorial entailment but, in contrast with results for classification type hierarchical responding, there was no consistent trend for TOF. Implications and future research directions are discussed.